Numerical simulation of transient temperature in flash butt-welded axi-symmetric circular sections. - Adedayo, Segun Mathew; Irehovbude, S. O. (Journal of Naval Architecture and Marine Engineering, 2013)
Thermal history along the length of a circular section subjected to flash-butt welding was analyzed by the finite difference method. A onedimensional nonlinear thermal numerical simulation using a computational model based on the finite difference approach is formulated taking into consideration fusion zone (FZ) temperature as a measure of heat input, ambient and initial temperature of rod. Flexibility of physical characteristics such as bar length, diameter and temperature dependency of thermal properties and variation of boundary conditions were applied. Peak temperatures of 490°C and 410°C were computed for a 20 mm external diameter solid and hollow pipes respectively at distance 5 mm from weld line. Preheat temperatures of 200°C and 400°C resulted into a 41.1% and 89.3% increase respectively in peak temperature as compared with non preheat conditions. The predicted values from this model compared reasonably with experimentally obtained thermal histories. DOI: http://dx.doi.org/10.3329/jname.v10i1.8683